Angka Kejadian Stunting Balita di Kecamatan Tanralili dan Tompobulu Kabupaten Maros - Malle, Sriwati; Rusli, Arham; Bachtiar Abdullahi, Alima; Wadi, Ahmad; Harifuddin, Harifuddin; Sani, Asrianti; Maruddin, Fatma (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Maros Regency occupies the 8th position in South Sulawesi province with a prevalence of stunted toddlers of 30.1% in 2022. This figure has experienced a significant decline of 7.1%, but this figure still allows for a spike in stunting cases. Data collection on the incidence of stunting in Tanralili and Tompobulu sub-districts is important in determining the prevalence of stunted toddlers in Maros district. The aim of this service activity is to obtain accurate data in the field which will be a reference for subsequent activities and to measure the nutritional status of toddlers affected by stunting and provide education to the community regarding stunting. From the results of the activity, it was found that the incidence of stunting in Tanralili sub-district was higher than in Tompobulu sub-district. Damai Village and Lekopancing Village are two villages with quite high stunting rates for toddlers in Tanralili sub-district, while in Tompobulu sub-district, this occurs in Tompobulu and Bonto Manurung villages. Education to the community is carried out during routine posyandu activities and through home visits. It is hoped that it will be able to reduce the incidence of stunting